Prototipo de lámpara LED sustentable con energía biofotovoltaica - Azuero Jaramillo, Luis Alfredo (2024)
The present research work focuses on the design and construction of a biophotovoltaic lamp, which seeks to explore the feasibility and efficiency of the energy produced by plants and microorganisms to light an LED lamp. The prototype mainly integrates clay PMFC cells with carbon, graphite and aluminum electrodes. In addition, it implements several cutting-edge technologies such as super capacitors, which stand out for their ultra-fast charging time, and SMD LED lights, which provide harmonious illumination with low energy consumption. However, the big challenge of biophotovoltaics is the low output currents, because the energy is obtained through the oxidation of biomass (exudates) rather than collecting energy directly from the photosystems. The latter method is more complex and in most cases directly harms the photosynthetic species, being an area of study still under development. The results of this research will encourage the development of new biophotovoltaic energy harvesting techniques based on the Redox effect, type of membrane, positioning and type of electrodes, thus expanding the field of renewable and sustainable energies. Keywords: Biophotovoltaics, BPV, electrodes, PMFC, MFC, redox.